(untitled) (Federal University Gusau Faculty of Education Journal, 2025)
The paper systematically reviewed the importance of integrating information and communication technology (ICT) tools in adult education programmes in Nigeria. This was informed by the revolution in access and distribution of information brought by ICT, which makes ICT an increasingly influential factor in human interaction and educational pursuit. Therefore, the paper examined the concepts of adult education and ICT. It also discussed importance and factors affecting usage of ICT in adult education before recommendations on how to maximise benefits of ICT in adult education were made. Such recommendations include the need for the government and other stakeholders to prioritise provision of adequate funds to adult education for purchase of necessary ICT equipment needed in adult education, the need for adult education centres to employ qualified and competent facilitators who are skilful in uses of ICT and the need for adult education centres to continuously provide in-service training and workshops to facilitators in order to improve their proficiency and productivity.